2022
DOI: 10.1111/jipb.13244
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a dmp based maternal haploid induction system for polyploid Brassica napus and Nicotiana tabacum

Abstract: Doubled haploid (DH) technology is used to obtain homozygous lines in a single generation, a technique that significantly accelerates the crop breeding trajectory. Traditionally, in vitro culture is used to generate DHs, but this technique is limited by species and genotype recalcitrance. In vivo haploid induction (HI) through seed is widely and efficiently used in maize and was recently extended to several other crops. Here we show that in vivo HI can be triggered by mutation of DMP maternal haploid inducer g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…From this starting point, protocols for some horticultural crops have been developed. In Brassica napus L., bnaDMP mutation could induce amphihaploidy [66,67]. In Nicotiana tabacum L., it was reported that the simultaneous MtDMP1, MtDMP2 and MtDMP3 mutations can trigger maternal haploidy at rates from 1.52% to 1.75% [68].…”
Section: In Vivo Haploid Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this starting point, protocols for some horticultural crops have been developed. In Brassica napus L., bnaDMP mutation could induce amphihaploidy [66,67]. In Nicotiana tabacum L., it was reported that the simultaneous MtDMP1, MtDMP2 and MtDMP3 mutations can trigger maternal haploidy at rates from 1.52% to 1.75% [68].…”
Section: In Vivo Haploid Inductionmentioning
confidence: 99%
“…In contrast, the inactivation of the MtDMP8 and MtDMP9 alleles in Medicago truncatula Gaertn would facilitate in vivo maternal haploid induction at a rate from 0.29% to 0.82% in mutant progeny [69]. Despite these results, the use of DMP genes is not very frequent because there are not transformation systems (CRISPR/Cas9) or TILLING populations in major crops [20,67].…”
Section: In Vivo Haploid Inductionmentioning
confidence: 99%
“…Knockout of ZmDMP results in a HIR of 0.1%-0.3% in maize, and mutations in DMP8 and DMP9 in Arabidopsis thaliana induced haploids at a rate of 2.1% ± 1.1% (Zhong et al, 2020). Mutations in DMP homologs also triggered HI in Medicago truncatula, tomato (Solanum lycopersicum), tobacco (Nicotiana tabacum), and B. napus (Wang et al, 2022;Zhong et al, 2022aZhong et al, , 2022b. However, no broad adaptation of the dmp-based HI line has been reported in B. napus, and whether there is functional redundancy among the four BnaDMP homologs has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…ZmPLA1 / MTL / NLD homologs have been identified only in monocots (Kelliher et al 2017 ; Yao et al 2018 ), but ZmDMP homologs were identified in both monocots and dicots (Zhong et al 2020 ). Although the utility of dmp mutants, for HI production, has been demonstrated in some dicot crops (Zhong et al 2020 , 2021 , 2022 ; Wang et al 2021 ), it remains unknown whether this approach is applicable for potato.…”
mentioning
confidence: 99%